A Survey on Computational Algorithms For Biological Data Analysis - Lakshmi, M.Muthu; Murugeswari, G (International Journal of Computer Sciences and Engineering, 2025)
Bioinformatics is an interdisciplinary field that uses the information technology algorithms for biological data analysis. Many tools and techniques have been investigated by the researchers for biological data interpretation, analysis and prediction. In accordance with the latest statistics, biological sequence analysis is one of the emerging areas in the field of Bioinformatics. In this paper, a survey on computational algorithms of Bioinformatics has been made. We analyzed the contributions made by the computer researchers for biological sequence analysis and survey is presented on various categories such as biological sequencing, alignment, compression and encoding, feature extraction, clustering and classification. The objective of the paper is to provide a deep understanding and knowledge regarding the existing computer algorithms used for biological data analysis and to identify the research areas for computer researchers in the field of bioinformatics